Comparison of prevalence of various ENT diseases and hearing impairment among children of government schools versus private schools of Mardan - Akram, Sumera; Khan, Muhammad Ahmed; Rehman, Abdul; Malik, Kamran Zamurrad; Afridi, Jehangir Ahmed; Akram, Sumera (Journal of Fatima Jinnah Medical University, 2021)
Background: School children are frequently afflicted with ENT diseases. The diseases and their associated complications, especially hearing impairment, can be devastating to the children and families alike. Socioeconomic status of children can have strong effect on frequency of various ENT diseases. The objective of this study is to compare the frequency of various ENT diseases among children studying in government schools versus those in private schools of district Mardan. Subjects and methods: A cross-sectional descriptive study was carried out at Mardan from July to December 2019. The researchers visited four schools (two government and two private schools) in Mardan district. Relevant history was obtained and physical examination was done to find out the frequency of various ENT diseases. The data variables (age, gender, ENT diseases, hearing impairment) were noted in research Performa and data was entered and analysed in SPSS 21 software. Frequencies were determine for age, gender and ENT diseases. Independent t-test was used to analyze quantitative variables, while Chi-square was used to analyze qualitative variables. A p-value less than 0.05 was taken as significant. Results: Total 2986 children were examined in 4 schools. The mean age of the children was 11 years. There were 56% boys and 44% girls. Total 2106 children were examined in two government schools and 880 children were examined in two private schools. The frequency of impacted cerumen was 18.4% (21.2% of government school children versus 11.4% of private school children; p<0.05). Frequency of allergic rhinitis was 9.7% (9.5% of government school children versus 10.1% of private school children; p=0.635). The frequency of chronic suppurative otitis media (CSOM) in government school children was 4.9% versus 2.5% among those in private schools (p<0.05). In this study cumulative prevalence of hearing impairment was 26.8%, where prevalence in government school children was 30.9% versus 17.2% in private schools (p-value<0.001). The causes of hearing impairment were impacted ear cerumen (68.3%), CSOM (15.7%), otitis externa (6.2%), OME (4.1%), otitis media (2.8%), congenital ear deformities (1.6%) and foreign bodies in ear (1.2%). The main causes of hearing impairment in majority of children were impacted cerumen and CSOM in 84% children. Conclusion: Various ENT diseases like impacted cerumen, rhinosinusitis, allergic rhinitis, pharyngitis, tonsillitis and CSOM are common in school going children. Impacted cerumen and CSOM are significantly more prevalent in government school children as compared to private schools which are primary cause of hearing impairment in children leading to significantly high prevalence of hearing impairment in government school children